Sympathetic and local vasoconstrictor response to cold in vibration induced white finger. Issue 4 (April 1985) - Olsen, N; Fjeldborg, P; Brchner-Mortensen, J
Abstract : To study the relative roles of sympathetic and local vasoconstrictor response to cold in vibration induced white finger (VWF) seven lumberjacks with bilateral VWF and seven age matched controls were investigated. During body cooling finger systolic blood pressure was measured with a cuff technique simultaneously on one affected finger on each hand at 30 degrees, 15 degrees, and 6 degrees C. Both affected fingers had an increased vasoconstrictor response at 15 degrees and 6 degrees C compared with the control group (p less than or equal to 0.05). During unilateral sympathetic nerve block the cold provocation test was repeated on both fingers. The unblocked finger affected by VWF showed no significant difference in the cold response between the two cold provocation tests (p greater than 0.10). The local cold response of blocked finger did not differ from that of the control group (p greater than 0.10). The sympathetic vasoconstrictor response to cold was estimated as the difference between the cold response before nerve block and the cold response during nerve block. The median sympathetic vasoconstrictor response at 6 degrees C was about twice as large as the local response during nerve block (p less than 0.05). The results indicate that the sympathetic vasoconstrictor response to cold plays the dominant part in VWF.